Problematika Sertifikasi Tanah Wakaf Masjid Di Kecamatan Kabila Bone - Dusa, Muslan K.; Faisal, Ahmad; Zainuddin, Asriadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
Waqf is a social act of worship that provides benefits to humanity, but it needs to be supported by certification to preserve its purpose. This article aims to identify and analyse the problems of certifying mosque waqf land in Kabila Bone Subdistrict. This research employs a descriptive qualitative approach in a field setting. The data sources comprise primary data collected through observation and interviews, as well as secondary data from statutory legislations, books, articles, and research results. The sample was determined through interviews using the purposeful sampling technique, employing a semi-structured interview model, with mosque administrators and the Religious Affairs Office in Kabila Bone Subdistrict. The results of the study indicate that the obstacles to implementing mosque land waqf certification in Kabila Bone Subdistrict are primarily due to a lack of coordination between mosque administrators and waqf donors (waqif), a limited understanding of the waqf certification mechanism, and incomplete administrative documents. Solutions to overcome these problems were implemented internally by the mosque administrators, who coordinated with the waqif and the Kabila Bone Subdistrict Religious Affairs Office, and externally by the Kabila Bone Subdistrict Religious Affairs Office through waqf socialisation.